THE CONTRIBUTION OF THE STUDENTS’ VOCABULARY, GRAMMAR AND PRACTICE ON THE ENGLISH SPEAKING COMPETENCY OF THE ELEVENTH GRADE OF THE SECOND YEAR STUDENTS OF SMUN 1 IN KUTA - Wendrajaya, H.; Seken,, I.K.; Marhaeni, A.A.I.N. (International Journal of Language and Literature, 2017)
This study aimed at investigating 1) the contribution of the students? vocabulary on the English speaking competency, 2) the contribution of the students? grammar on the English speaking competency, 3) the contribution of the students? practice on the English speaking competency, and 4) the contribution of the students? vocabulary, grammar and practice on students? speaking competency. The present research makes use of an ex post facto study with regression analysis. The research was done toward the second year or eleventh grade students of SMUN 1 Kuta in academic year 2013/2014. The population of the study covered 398 students; and the sample was 80, which was determined through cluster random sampling technique. This research used multiple regression analysis with two kinds of instruments, that is, tests and questionnaire. The results show that: 1) there is a significant contribution of vocabulary on the students? speaking competency at 26.8%, 2) there is a significant contribution of grammar on the students? speaking competency at 18.1%, 3) there is a significant contribution of practice on the students? speaking competency 16.9%, 4) there is a significant contribution of vocabulary, grammar and  practice on the students? speaking competency at 32.6%. Based on the results of this study, the teachers were suggested that they develop various ways to teach vocabulary, grammar and practice to improve the students? speaking competency.